2012
DOI: 10.1111/j.1464-410x.2012.10944.x
|View full text |Cite
|
Sign up to set email alerts
|

Under‐grading of <4 cm renal masses on renal biopsy

Abstract: Study Type – Prognosis (case series) Level of Evidence 4 What's known on the subject? and What does the study add? It is well documented that biopsy of small renal masses is inaccurate and tends to under‐estimate tumour grade compared with surgical specimens. To our knowledge there has not been a study showing grading discrepancy between biopsy and surgical excision in a large population‐based cohort. OBJECTIVE To determine whether differences exist in tumour grade between patients who undergo partial nephrec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…A recent large series of 405 biopsies showed concordant Fuhrman nuclear grades in preoperative biopsies and nephrectomy specimens in only 38.3% . Most contemporary reviews and series conclude that Fuhrman nuclear grading has lower accuracy in renal biopsies …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent large series of 405 biopsies showed concordant Fuhrman nuclear grades in preoperative biopsies and nephrectomy specimens in only 38.3% . Most contemporary reviews and series conclude that Fuhrman nuclear grading has lower accuracy in renal biopsies …”
Section: Discussionmentioning
confidence: 99%
“…Most discrepancies in nuclear grade are within one grade and are most likely due to tumor heterogeneity . Millet et al reported an improved concordance in nuclear grading using a 2‐tiered simplified Fuhrman classification (Fuhrman I‐II = low grade; Fuhrman III‐IV = high grade) over a 4‐tiered Fuhrman classification .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These phenomena may have accounted for the findings of Harris et al. suggesting under‐grading of RCC on biopsy compared with final pathology.…”
Section: Resultsmentioning
confidence: 93%
“…El flujo constante de sangre a temperatura corporal condiciona un enfriamiento de partes del tumor adyacentes a los vasos sanguíneos. Debido a estos limites para alcanzar picos de temperatura y de duración adecuada es por lo que los resultados en cuanto a ablación completa de este tipo de tumores son inferiores y en gran medida precisan la aplicación de un número mayor de sesiones de RF(Beland et al 2011),(Karam et al 2011),(Okhunov et al 2012),(Park et al 2010),(Patel et al 2013),(Prevoo et al 2010),(Velasco et al n.d.),(Zhang et al 2012),(Zurera et al n.d.).Siguiendo las indicaciones de la Asociación Europea de Urología (EAU), la biopsia renal debe realizarse en los siguientes supuestos(Aribaş et al 2011),(Fotiadis & Matson 2009),(Harris et al 2012),(Klingler & Susani 2010),(Kyle et al 2008), (Ortiz-Alvarado & Anderson 2010),(Pandharipande et al 2010),(Remzi & Marberger 2009),(Tan et al 2012):…”
unclassified